Overview of the Rocket Experiment for Neutral Upwelling Sounding Rocket 2 (RENU2). Issue 21 (26th October 2020) - Lessard, Marc R.; Fritz, Bruce; Sadler, Brent; Cohen, Ian; Kenward, David; Godbole, Niharika; Clemmons, James H.; Hecht, James H.; Lynch, Kristina A.; Harrington, Meghan; Roberts, Thomas M.; Hysell, David; et al.
Abstract: The Rocket Experiment for Neutral Upwelling 2 (RENU2) rocket was launched on 13 December 2015 at 07:34 UT. The payload transited the cusp region during a neutral upwelling event, supported by a comprehensive set of onboard and ground‐based instrumentation. RENU2 data highlight two important processes. One is that a proper understanding of neutral upwelling by Poleward Moving Auroral Forms (PMAFs) requires a treatment that mimics the quasiperiodic passage of a sequence of PMAFs. As a PMAF reaches a flux tube, its physical consequences must be determined including the residual history of effects from previous passages, implying that understanding such a process requires an accounting of the system hysteresis. Second, RENU2 observations suggest that neutral density enhancements driven by precipitation and/or Joule heating can be highly structured in altitude and latitude. In addition, timescales involving neutral dynamics suggest that the structuring must be slowly changing, for example, over the course of 10 to tens of minutes. Key Points: RENU2 measured particles and fields within a PMAF‐driven neutral upwelling event PMAFs consist of multiple thin arcs; poleward motion leads to a quasiperiodic heating process Neutral upwelling (driven by soft precipitation) is dynamic and highly structured in space